Comparison of joint kinematics from optical marker-based and inertial sensor-based motion capture during change-of-direction movements - Mareike Kühne; Peter Federolf; Diego Jaén-Carrillo; Katharina Schiel; Maurice Mohr (Bern Open Publishing, 2024)
The development of inertial measurement units (IMUs) has opened up possibilities to test kinematics of sports movements in natural environments (Di Paolo et al., 2023). This advantage over lab-based optical motion capture (OMC) comes at the cost of inherent inaccuracies. Especially, fast multidirectional movements including de- and accelerations pose a challenge for inertial-based movement reconstruction with limited task-specific validation research available (Heuvelmans et al., 2022). Therefore, we aimed to test the validity of IMU-based kinematics in a 180° change of direction (COD) task to provide insight into the applicability for future on-field ACL injury risk research. Twenty-six sports science students were equipped with eight IMU sensors of the Noraxon Ultium Motion System and an adaption of the Plug-in-Gait markerset (53 markers) recorded by a VICON OMC system. They performed five 180° anti-clockwise CODs at their maximum speed. As an example for sagittal and frontal plane angles relevant for ACL injury risk, the knee flexion and abduction angle at the initial contact of the cutting step (right leg) were calculated using the Noraxon MyoMotion software for IMU-recorded data and OpenSim for marker-based OMC data. At the time of abstract submission, the data of five (randomly chosen) participants had been analysed. More participants and more joint angle outcomes will be included in follow-up analyses. Deviations between IMU-generated and OMC-generated joint angles are depicted in Figure 1. Within subjects, deviations below 1.5 standard deviations were observed. Between subjects, deviations ranged from 0° and 22° in knee flexion angles and 0° and 11° in knee abduction angles. A general trend towards higher joint angles measured by the IMU system is noticeable, suggesting a possible off-set error. For four out of five participants, the knee flexion deviation was below 10°, which can be considered an accuracy which is tolerable but requires consideration in the interpretation (< 2°: good accuracy, 2-5°: acceptable accuracy, 5-10°: tolerable accuracy, > 10° unbearable accuracy; Bessone et al., 2022). Deviations in knee abduction angles appear too large given the small physiological joint range and motion in this plane. This preliminary analysis of individual deviations suggests acceptable deviations between IMU and OMC measurements regarding knee flexion but problematic deviations for knee abduction. Prospectively, we aim to investigate possible off-set corrections, e.g. through a better alignment of the underlying biomechanical models, and alternative approaches for IMU-based movement reconstruction, e.g. through optimal control simulations (Nitschke et al., 2024). References Bessone, V., Höschele, N., Schwirtz, A., & Seiberl, W. (2022). Validation of a new inertial measurement unit system based on different dynamic movements for future in-field applications. Sports Biomechanics, 21(6), 685-700. https://doi.org/10.1080/14763141.2019.1671486 Di Paolo, S., Nijmeijer, E., Bragonzoni, L., Dingshoff, E., Gokeler, A., & Benjaminse, A. (2023). Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention. European Journal of Sport Science, 23(5), 859-868. https://doi.org/10.1080/17461391.2022.2064771 Heuvelmans, P., Benjaminse, A., Bolt, R., Baumeister, J., Otten, E., & Gokeler, A. (2022). Concurrent validation of the Noraxon MyoMotion wearable inertial sensors in change-of-direction and jump-landing tasks. Sports Biomechanics. Advance online publication. https://doi.org/10.1080/14763141.2022.2093264 Nitschke, M., Dorschky, E., Leyendecker, S., Eskofier, B. M., & Koelewijn, A. D. (2024). Estimating 3D kinematics and kinetics from virtual inertial sensor data through musculoskeletal movement simulations. Frontiers in Bioengineering and Biotechnology, 12, Article 1285845. https://doi.org/10.3389/fbioe.2024.1285845